(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe caregiver burden and examine factors associated with high caregiver burden among primary caregivers of patients after breast cancer surgery at Nghe An Oncology Hospital in 2025. Methods: An analytical cross-sectional study with prospective data collection was conducted among 102 unpaid primary caregivers at the Breast Surgery Department, Nghe An Oncology Hospital. Caregiver burden was assessed using the 22-item ZBI. High burden was defined as a ZBI score above 60. Descriptive statistics and the Chi-square test were used for analysis. Patients’ daily living activities were assessed using the Katz ADL scale. Patients were categorized into 2 groups: independent (Katz ADL = 6 points) and dependent (Katz ADL < 6 points). Results: The mean ZBI score was 57.13 ± 15.62 (range: 29-73). High caregiver burden was observed in 53.9% of participants and moderate burden in 27.5%. The proportion with high burden was greater among caregivers aged ≥ 60 years than among those aged under 60 years (80.9% vs. 30.9%; p < 0,001). Caregiver burden was also associated with the patient’s functional status (p < 0,001). Conclusions: Caregiver burden after breast cancer surgery was substantial. Older caregivers and caregivers of functionally dependent patients should be prioritized for burden screening, counseling, and supportive interventions.